Trends and issues affecting workforce planning in New Zealand university libraries - Barthorpe, Gillian (Auckland University of Technology, 2012)
University libraries are facing transformational changes in order to remain relevant and meet the needs of their users in the 21st century. This study investigated the trends and issues affecting workforce planning in New Zealand university libraries. New Zealand university library senior managers and younger staff were interviewed to draw on their insights and understanding of these trends and issues taking the New Zealand context into account. An examination of the literature found similarities between New Zealand and other parts of the world with regard to the technological developments and changes in scholarly publishing models that are impacting on university libraries. This has and will continue to impact on the services offered, both in the physical and virtual environments, as well as the skills and competencies required by library staff to meet these needs. Within the Zealand tertiary education context cognisance needs to be taken of the identified priorities to increase the country’s research profile and improve the productivity levels of an increasingly diverse population. This is underpinned by the government funding model which is unlikely to benefit from any significant increase in light of the current global economic situation. Workforce planning has become increasingly important to ensure that university libraries have staff with the appropriate skills and competencies to meet these changing needs in the future. The impact of the ageing workforce working for longer as well as the impending retirement of many of this cohort in the next ten to fifteen years presents challenges and opportunities for libraries. The recruitment of new staff to the library profession as well as the relevance of the present professional qualifications were identified as issues of concern. Succession planning and the provision of career development opportunities for these staff, particularly in the area of leadership and management development are essential to ensure that they are retained.
Keywords: Workforce planning; New Zealand; University libraries; Ageing workforce; Career development; Succession planning; Leadership; Management; Library of the future